The operational management and marketing techniques used to persuade Customer at Zirkoh Bar, Timog Quezon City - Galon, Ronaldo P. (Manila : National University, 2008)
The focus of this study is the managerial operation of Zirkoh bar located in Timog Quezon City.
Table of Contents -- Chapter 1. Problem and its Background -- Chapter 2. Review of Related Literature and Studies -- Chapter 3. Research Methodology and Procedure -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary of Findings, Conclusions, and Recommendations -- Appendices.
Research Method : Descriptive Research Design
Includes bibliographical references.